2019
DOI: 10.1038/s41598-019-39199-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between multi-component myelin water fraction, T1w/T2w ratio, and diffusion tensor imaging measures in healthy human brain structures

Abstract: Various MRI techniques, including myelin water imaging, T1w/T2w ratio mapping and diffusion-based imaging can be used to characterize tissue microstructure. However, surprisingly few studies have examined the degree to which these MRI measures are related within and between various brain regions. Therefore, whole-brain MRI scans were acquired from 31 neurologically-healthy participants to empirically measure and compare myelin water fraction (MWF), T1w/T2w ratio, fractional anisotropy (FA), axial diffusivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 62 publications
11
109
0
Order By: Relevance
“…In NAWM, no significant correlation was found. All these studies concluded that the different quantitative techniques are at least partially correlated with each other but are sensitive to different aspects of the pathology and may provide complementary information about underlying brain tissues [53].…”
Section: Discussionmentioning
confidence: 99%
“…In NAWM, no significant correlation was found. All these studies concluded that the different quantitative techniques are at least partially correlated with each other but are sensitive to different aspects of the pathology and may provide complementary information about underlying brain tissues [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although the acquisitions of these contrasts can be achieved faster and with enhanced resolution in comparison to the other approaches, other microstructural features unrelated to myelin density were shown to affect these contrasts. 65,66 The proposed framework and our study setup have limitations. The undersampling introduces a slight blurring of the images, as shown in the comparison of MWF MESE and MWF GRASE maps.…”
Section: Discussionmentioning
confidence: 99%
“…However, while Uddin et al (2018) cite low correlations between T1w/T2w and a histologically validated technique for examining myelin, myelin water fraction (MWF), for white matter structures, they nonetheless cite moderate correlations for subcortical gray matter structures (Uddin et al, 2018(Uddin et al, , 2019. Thus, a conservative approach for using the T1w/T2w signal ratio is its use as a nonspecific biomarker of microstructure, with the use of quantitative MRI techniques, such as magnetization transfer or myelin water imaging, to parse out the effect of differential elements of the microstructure, such as myelin using MWI and iron using R2* (the short spin-spin T2 relaxation; Péran et al, 2007;Stüber et al, 2014).…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%